1974
DOI: 10.1002/art.1780170311
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilus influenzae septic arthritis. A mimicker of gonococcal arthritis

Abstract: The rare occurrence of septic arthritis due to Hemophilus influenzae in an adult with systemic lupus erythematosus is reported. The clinical presentation mimicked disseminated gonococcemia with associated gonococcal arthritis. The features of this case as well as other bacterial infections known to cause confusion with gonococcal arthritis are reviewed, and the clinical and laboratory characteristics of septic arthritis caused by H influerrzae are described.In children, infections from Type B Hemophilus influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It was suggested that this was the result of aggressive antibiotic therapy in early childhood 6 . However, adults with demonstrable bactericidal antibodies have developed bacteremic HI infections 7,8 . Therefore, it doesn't seem probable that HI antibodies play an important role in the protection against severe HI infections.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that this was the result of aggressive antibiotic therapy in early childhood 6 . However, adults with demonstrable bactericidal antibodies have developed bacteremic HI infections 7,8 . Therefore, it doesn't seem probable that HI antibodies play an important role in the protection against severe HI infections.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first case of pseudopodagra due to Hemophilus influenza and only the thirteenth reported case of hemophilus pyarthrosis in an adult (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In Huskisson's classic paper on pseudopodagra, fourteen causes of podagra other than gout are recorded, including infection (1 3).…”
mentioning
confidence: 95%